Megascolia (Regiscolia) bidens (Hymenoptera: Scoliidae), a new distributional record for Continental Greece - Demetriou, Jakovos; Gastouniotis, Georgios; Castagnet, Jean Baptiste; Koutsoukos, Evangelos (ENTOMOLOGIA HELLENICA, 2021)
Megascolia (Regiscolia) bidens (Linnaeus, 1767) (Hymenoptera: Scoliidae), previously known to inhabit Dodecanese Islands, is recorded for the first time in the Saronic Gulf and Greek mainland. The species distribution and ecology are briefly discussed. A short species diagnosis is provided to assist further data collection.